4(3x+-5)+6=7(x-2)+6x

Simple and best practice solution for 4(3x+-5)+6=7(x-2)+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x+-5)+6=7(x-2)+6x equation:


Simplifying
4(3x + -5) + 6 = 7(x + -2) + 6x

Reorder the terms:
4(-5 + 3x) + 6 = 7(x + -2) + 6x
(-5 * 4 + 3x * 4) + 6 = 7(x + -2) + 6x
(-20 + 12x) + 6 = 7(x + -2) + 6x

Reorder the terms:
-20 + 6 + 12x = 7(x + -2) + 6x

Combine like terms: -20 + 6 = -14
-14 + 12x = 7(x + -2) + 6x

Reorder the terms:
-14 + 12x = 7(-2 + x) + 6x
-14 + 12x = (-2 * 7 + x * 7) + 6x
-14 + 12x = (-14 + 7x) + 6x

Combine like terms: 7x + 6x = 13x
-14 + 12x = -14 + 13x

Add '14' to each side of the equation.
-14 + 14 + 12x = -14 + 14 + 13x

Combine like terms: -14 + 14 = 0
0 + 12x = -14 + 14 + 13x
12x = -14 + 14 + 13x

Combine like terms: -14 + 14 = 0
12x = 0 + 13x
12x = 13x

Solving
12x = 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.
12x + -13x = 13x + -13x

Combine like terms: 12x + -13x = -1x
-1x = 13x + -13x

Combine like terms: 13x + -13x = 0
-1x = 0

Divide each side by '-1'.
x = 0

Simplifying
x = 0

See similar equations:

| 5x+7-2x+1=17 | | 3x-3+x-7+x=180 | | 4(3x+-5)+6=6x+2(3x-8) | | (4y+7)(9-y)=0 | | 3+4k-3k= | | x-(-2)=-7 | | -7y+5=8y+8 | | 4(3x+-5)+6=12x-14 | | 91-2x=9x-162 | | 5(9+-5.5)+3y=-4 | | 8x+11=6x+13 | | 2m+(-8m)= | | 5y-6x=-13 | | 4/5+1/8= | | (5n-20)=3n | | -x-6=-2x-1 | | D+5=3 | | 3k^2-10k+3=0 | | x+2=48 | | 256x+1=125x-2 | | 2/3x-1+1/6=9 | | 6x^3+14x^2-21x-49=0 | | x=3x+6x | | x=3x-6x | | x=3x-5-5x-26 | | 4-(12+z)=192 | | y-8=(x-6) | | x=3x-5+5x-26 | | 12y+8=24 | | 3(x-5)=x+8-5 | | r+31=17 | | 9=-4+v |

Equations solver categories